A case of CD138−/CD19+/CD4+ IgD plasma cell leukemia. (9th April 2014) - Sorigue, Marc; Juncà, Jordi; Gassiot, Susanna; Millá, Fuensanta; Mate, José‐Luis; Navarro, Josep Tomàs
<x xml:space="preserve">Abstract</x> Background Plasma cell leukemia (PCL) is an uncommon and aggressive disease caused by the clonal proliferation of atypical plasma cells with phenotypical abnormalities similar to those seen in multiple myeloma (MM), although at different rates. Here, we report a case of IgD PCL with a very unusual CD138−/CD19+/CD4+ phenotype. Methods Peripheral blood and bone marrow samples from a 37‐year‐old patient afflicted by an aggressive plasma cell dyscrasia were examined and analyzed by conventional morphology, flow cytometry, and immunohistochemistry. Results Analysis of peripheral blood fulfilled criteria for PCL (more than 20% and more than 2 × 10e9 cells/L). However, flow cytometry and immunohistochemistry phenotyping revealed that the cells were CD138−/CD38+/CD19+/CD4+/CD56−/CD117−. Conclusions PCL is diagnosed on peripheral blood smear. Immunophenotyping is a tool that can be helpful in diagnosing difficult cases but its atypical findings should not prevent the appropriate PCL diagnosis in clinically and morphologically unquestionable cases. © 2014 International Clinical Cytometry Society